Correction to: Neighborhood socioeconomic disadvantage is associated with multimorbidity in a geographically-defined community - Alanna M. Chamberlain; Lila J. Finney Rutten; Patrick M. Wilson; Chun Fan; Cynthia M. Boyd; Debra J. Jacobson; Walter A. Rocca; Jennifer L. St Sauver (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.